2012
DOI: 10.1021/jm300317k
|View full text |Cite
|
Sign up to set email alerts
|

Novel Steroid Inhibitors of Glucose 6-Phosphate Dehydrogenase

Abstract: Novel derivatives of the steroid DHEA 1, a known uncompetitive inhibitor of G6PD, were designed, synthesized, and tested for their ability to inhibit this dehydrogenase enzyme. Several compounds with approximately 10-fold improved potency in an enzyme assay were identified, and this improved activity translated to efficacy in a cellular assay. The SAR for steroid inhibition of G6PD has been substantially developed; the 3β-alcohol can be replaced with 3β-H-bond donors such as sulfamide, sulfonamide, urea, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 42 publications
2
53
0
Order By: Relevance
“…14B). The proton NMR spectrum of the isolated P450 17A1 product also matched a previously reported NMR spectrum of synthetic 16␣-hydroxy-DHEA (45).…”
Section: P450 17a1 Reactions With Iodosylbenzene-preliminarysupporting
confidence: 82%
“…14B). The proton NMR spectrum of the isolated P450 17A1 product also matched a previously reported NMR spectrum of synthetic 16␣-hydroxy-DHEA (45).…”
Section: P450 17a1 Reactions With Iodosylbenzene-preliminarysupporting
confidence: 82%
“…In contrast, G6PD-deficient tumor cell lines showed relatively slow growth and enhanced apoptosis [41]. Previous studies also reported G6PD inhibitory properties for few compounds such as steroids and derivatives [42,43], chalcones [28], catechin gallates [44], and some phenolic molecules [45].…”
Section: Resultsmentioning
confidence: 96%
“…The first one relies on cell treatment with the steroid hormone dehydroepiandrosterone (DHEA). In DHEA-treated cells, inhibition of glucose-6-phosphate dehydrogenase activity resulted in decreased levels of NADPH, an essential cofactor that helps maintain glutathione (GSH) in its reduced antioxidant form (54). Thus, decreased levels of GSH weaken the cell's antioxidant defense system.…”
Section: Analysis Of Binding Of Recombinant Egfp-ply and Egfp-⌬6plymentioning
confidence: 99%